Membangun Minat Baca Siswa SD Melalui Penguatan Literasi Membaca - Riyan Hasif Perdana; Lulu Amelia Rahma; Vemita Rahmasari; Intan Audy Setianingrum; Madu Mukti Migunani; Delia Indrawati; Helda Kusuma Wardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Reading literacy in elementary schools remains a major problem in Indonesia, demonstrated by students' low ability to comprehend, analyze, and draw conclusions from reading material. Although the School Literacy Movement (GLS) has been implemented, its effectiveness tends to decline due to a lack of varied and engaging reading materials. Therefore, integration of literacy programs with learning media appropriate to student characteristics is necessary. This study aims to analyze the effectiveness of integrating the School Literacy Movement (GLS) and picture storybooks in improving elementary school students' reading literacy. The method used was a literature review, with data collection techniques through searching national journal articles in the Google Scholar and SINTA databases for the period 2021-2026. Data were analyzed using content analysis techniques through in-depth reading, grouping, comparison, and synthesis of research findings. The study results indicate that GLS is effective in developing sustainable reading habits, while picture storybooks can increase students' interest and understanding through visual stimuli. The integration of these two approaches has proven to be more optimal than their separate implementations. Therefore, it is recommended that schools manage the GLS program innovatively by providing a variety of reading materials, particularly picture books, to create a more effective and sustainable literacy culture. Furthermore, the results of this study are expected to serve as a foundation for further research to develop more integrated, contextual, and sustainable literacy models in the future.